STRATEGI MANAJEMEN HUMAS SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMA NEGERI 1 KOTA JAYAPURA - Sahrul Akbar; Muh. Riswan; Erry Ersani; Listiady Gustian; Anisya Indria Nurhidayati Anshari (Jurnal Manajemen Pendidikan, 2026)
Objective: The study aims to uncover the public relations strategy of school public relations in improving the quality of education at SMA Negeri 1 Kota Jayapura. This study uses a case study approach to explore more deeply the role and strategy of school public relations management in improving the quality of education. Research data were collected through observation, in-depth structured interviews and documentation then analyzed using the Miles and Huberman model. The results of this study indicate that the public relations management strategy of school public relations at SMA Negeri 1 Kota Jayapura has a significant contribution in improving the quality of education through a holistic and integrated approach. The strategy for improving the quality of education is implemented through the role of public relations as a facilitator for other areas of school management, an initiator of collaboration, and a forum for aspirations of various internal and external parties. Public relations at SMA Negeri 1 Kota Jayapura manages information effectively, builds good relationships with various parties, and creates a strong partnership network to support quality education. This school public relations practice can be a model of good practice in school public relations management governance in improving the quality of education. This study provides an empirical contribution regarding good practices in school public relations management based on local Papuan cultural wisdom that can be applied in other schools.